The Beauty and The Beast of Rural Education Development in Northern Malaysia - Nazmi Noordin; Kamarudin Ngah (Asian Social Work Journal, 2019)
Education will lead to the economic growth, stability of social and political system, able to reduce crime rates and at the same time will improve social services. Education is very important for rural folks especially among young people in improving their standard of living. Poor and lack of education will spoil all other effort towards rural development. When rural people schooling, it will open a lot of opportunities for them in exploring the wider world. Education contribute in developing appropriate skills among the communities and individuals in facing the challenges in their life. Both formal and non-formal education are important in giving an opportunity to the people to excel in their life. Formal education is said to be a foundation in developing some skills while non-formal education more advantageous in some situation. The purpose of this study is to identify the improvement and the pitfall of education development in rural area in Northern Malaysia especially in Kedah, Malaysia. Mix methods were applied where 240 households from selected rural village answered a questionnaire distributed to them and another thirteen (13) headman and six (6) development managers were interviewed for the data collection. Mean value was used in explaining the finding for the quantitative method while Hermeneutic Analysis was used for the qualitative method. The findings discussed on the improvement as well as pitfalls of education development in rural area.